Evidence that Acetonitrile is Sensitive to Different Interaction Sites of Ionic Liquids as Revealed by Excess Spectroscopy. Issue 10 (21st March 2017) - Zhou, Yu; Zheng, Yan‐Zhen; Zhang, Tian; Deng, Geng; Yu, Zhi‐Wu
Abstract: By studying the interactions between an ionic liquid, 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide, and a co‐solvent acetonitrile, the C≡N stretching vibration is found to be sensitive to different interaction sites as shown by excess infrared spectroscopy. Four existing forms of acetonitrile molecules are identified and a detailed transformation process of the ionic liquid upon dilution is obtained. Such characteristics of the nitrile group are discussed from the viewpoint of its ability to form hydrogen bonds with proton donors. It is believed that this is due to the intermediate charge donating ability of the C≡N group as compared with other groups such as S=O, CH3, and aromatic C−H. Abstract : Everything in excess : The C≡N stretching vibration is found to be sensitive to different interaction sites as shown by excess infrared spectroscopy. Four existing forms of acetonitrile molecules are identified and a detailed transformation process of the ionic liquid upon dilution is revealed. Such characteristics of the nitrile group are discussed with respect to its ability to form hydrogen bonds with proton donors.